Vitamin D and autoimmunity. (1st November 2016) - Rosen, Y; Daich, J; Soliman, I; Brathwaite, E; Shoenfeld, Y
Abstract : Objectives : To review and evaluate the role of vitamin D in autoimmune diseases based on current studies. Method : We searched PubMed using keywords such as 'vitamin D', 'autoimmune disease', and 'autoimmunity'. We compiled and reviewed various studies including prospective cohorts, cross-sectional studies, longitudinal evaluations, genetic studies, and experimental models that investigated the role of vitamin D in autoimmune diseases. Results : There is evidence based on these various studies that several key autoimmune diseases are modulated by vitamin D. These diseases include, but are not limited to, multiple sclerosis (MS), scleroderma or systemic sclerosis (SSc), autoimmune thyroid diseases, rheumatoid arthritis (RA), and primary biliary cirrhosis (PBC). Conclusions : Although there is evidence for vitamin D as a factor in the pathophysiology of autoimmune diseases, the mechanism for this association has yet to be elucidated. Additional data are needed to corroborate these findings.